Emerging Concepts in Therapeutic Interventions for Idiopathic Pulmonary Fibrosis - Schott, Cody A.; Mohning, Michael P.; Cooley, Joseph C. (Seminars in Respiratory and Critical Care Medicine, 2025)
Idiopathic pulmonary fibrosis (IPF) is a rare but devastating diagnosis for patients with only two approved drug therapies. Extensive preclinical studies have identified and characterized novel pathways driving IPF pathogenesis, and researchers have identified several new promising therapeutic targets to help treat IPF. However, translating these preclinical models into viable treatment modalities has proven challenging. This review will address the evolving nature of IPF research, examine the preclinical studies and their target pathways that have advanced to clinical trials, and address the translational gap that has limited the success of novel therapeutic trials for IPF.
Keywords: idiopathic pulmonary fibrosis; interstitial lung disease; anti-fibrotic; preclinical models; pulmonary fibrosis